PENATALAKSANAAN FISIOTERAPI PADA KASUS ISCHIALGIA ET CAUSA SPONDYLOLISTHESIS DENGAN MODALITAS TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN TERAPI LATIHAN DI RSUD BANDUNG KIWARI. - Maulana Sadeli, Mochammad; Rahman, Ika; Thesalonika, Lona (Jurnal Infokes, 2023)
Spondylolisthesis is a condition in which one vertebral body slips forward. This condition is one of the causes of low back pain (LBP), which can be caused by degenerative, ischemic, congenital, traumatic, pathological, or iatrogenic factors resulting from lumbar decompression surgery. To determine the physiotherapy management in reducing pain, increasing muscle strength, improving joint range of motion, and functional ability in patients with spondylolisthesis using transcutaneous electrical nerve stimulation and strengthening and stretching exercises. After 6 physiotherapy sessions, there was a decrease in pressure pain scores from T1: 2 to T6: 0, movement pain from T1: 4 to T6: 2, an increase in lumbar flexion muscle strength scores from T1= 3+ to T6= 5, lumbar extension from T1=4 to T6=5, hip flexion T1=3+ to T6=5, an increase in joint range of motion in lumbar flexion from T1: 70o to T6: 80o , lumbar extension from T1: 20o to T6: 25o , hip flexion T1=110o to T6=120o, increased functional activity examination score from T1: 26% to T6: 12%. Transcutaneous electrical nerve stimulation, ultrasound, and strengthening and stretching exercise therapy can reduce pain, increase muscle strength, and improve joint range of motion in cases of sciatica due to spondylolisthesis